STRATEGI KOMUNIKASI PEMASARAN PADA THE TRANS RESORT BALI - Komang Alicia Trisnayanti; I Made Widiantara; Ni Ketut Suciani (ADISAM PUBLISHER, 2026)
Tourism is one of the main pillars of the Bali regional economy that drives fierce competition in the hotel accommodation sector. Established in 2014 and located in a strategic and easily accessible area, The Trans Resort Bali positions itself with the positioning statement